Role of Union Parishads in Ensuring Child Education in Bangladesh during flood- a Qualitative Study - Yasmin Parvin Tibriji; Md Khaled Bin Chowdhury (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Governments ratifying the United Nations Conventions on the Rights of the Children   have responsibility to ensure   the rights of children to education in every situation.  Bangladesh being a disaster-prone country faces flood and struggles with its consequences every year. During flood children are deprived of education along with many other basic rights in Bangladesh. But the fact is that there is scanty research on the scale of infrastructural and learning loss caused to primary education as a result of flood. So, our study firstly investigates the scale of damage to primary education institutions and the consequent learning loss at the said level.  It is also a fact that there are different steps to mitigate the negative effects of flood   on primary education. But without the participation of   grass root level local government authority, it is not easy to solve the problem. As a grass root level local government institution, the Union Parishad and its Disaster Management Committee should minimize the effect of flood on primary education and ensure the children’s right to education. But it is assumed that the Union Parishads do not perform this duty properly. So, our research also investigates whether the Union Parishads are performing their mandated responsibilities in this regard. We have followed a qualitative research method depending on interviews with two types of samples, field visit and document review. The interviews with both ten Head Teachers and ten Managing Committee members were conducted. The research indicates that Union Parishads are not doing their assigned duties of ensuring primary education during flood. The research recommends that in addition to developing the infrastructural facilities, the concerned committees of the UPs need to be proactive and more sincere about continuing primary education during and after flood